Implementation of The Desmos Application in Learning Functions to Enhance Students' Conceptual Understanding - Mirunnisa, Mirunnisa; Razi, Zulfa (Tematik : Jurnal Konten Pendidikan Matematika, 2025)
Understanding the concept of functions is a fundamental aspect of mathematics education, which often poses challenges for students due to its abstract nature. The utilization of software-based learning technology, such as the interactive and user-friendly Desmos application, can support the learning process with rich graphical visualizations, thereby enhancing student engagement and understanding. This article examines the implementation of the Desmos application in function learning at the high school level, focusing on improving students' conceptual understanding. Through quantitative and qualitative research involving 60 eleventh-grade students, it was found that the use of Desmos significantly improved learning outcomes, motivation, and student learning activities. These findings imply the need for integrating visualization technology into mathematics education to effectively support the learning of abstract concepts.